2016
DOI: 10.1007/s00018-016-2386-8
|View full text |Cite
|
Sign up to set email alerts
|

The cystic fibrosis transmembrane conductance regulator (CFTR) and its stability

Abstract: The cystic fibrosis transmembrane conductance regulator (CFTR) is responsible for the disease cystic fibrosis (CF). It is a membrane protein belonging to the ABC transporter family functioning as a chloride/anion channel in epithelial cells around the body. There are over 1500 mutations that have been characterised as CF-causing; the most common of these, accounting for ~70 % of CF cases, is the deletion of a phenylalanine at position 508. This leads to instability of the nascent protein and the modified struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 88 publications
(103 reference statements)
3
42
0
2
Order By: Relevance
“…The multidomain complexity and highly dynamic nature of the channel, together with CFTR’s intrinsic instability, particularly in detergents, make its study especially challenging [35,45,54,57]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The multidomain complexity and highly dynamic nature of the channel, together with CFTR’s intrinsic instability, particularly in detergents, make its study especially challenging [35,45,54,57]. …”
Section: Discussionmentioning
confidence: 99%
“…A stable and monodisperse protein is the key to higher resolution structures whether by cryo-EM or crystallography, and also for biochemical and biophysical studies to probe the energetics, dynamics and mechanism of action that cannot be revealed by structure alone. However, the low stability of CFTR in detergent solution, and even more so ΔF508-CFTR and other folding mutations, has impeded progress [35]. …”
Section: Introductionmentioning
confidence: 99%
“…Importantly, a comparison of the four (WT, ΔF508, ΔF508+V510D and ΔF508+R1070W) 1 µs MD simulations also demonstrated a strong correlation between in silico protein stability and published experimental data such as secondary structure stability (WT ~ ΔF508+V510D >> ΔF508+R1070W > ΔF508), and supported a proposed salt-bridge interaction between V510D and R1070 at the NBD1:ICL4 interface (28,29). These results also support previously made predictions regarding increased solvent exposure of the V510 loop in the V510D mutant (15).…”
Section: Quality Analysis For Molecular Dynamics Simulationsmentioning
confidence: 62%
“…Interestingly, the origins of the capture and insertion of the R domain in CFTR are unknown as no significant sequence homology with other proteins has been found to date. 36 PKA phosphorylation sites are highly conserved among species, and the R region has been shown to contain the majority of those sites. 36,37 This region may be likened to a net or web structure that is highly plastic with subregions of disorder and coil where transitions occur between these states when targeted by PKA and other protein kinases.…”
Section: Cftr Protein Structure Remains To Be Fully Elucidatedmentioning
confidence: 99%
“…36 PKA phosphorylation sites are highly conserved among species, and the R region has been shown to contain the majority of those sites. 36,37 This region may be likened to a net or web structure that is highly plastic with subregions of disorder and coil where transitions occur between these states when targeted by PKA and other protein kinases. One idea is that a randomly fluctuating R region becomes locally ordered with coil structures after regulation to permit the binding of other proteins to assemble a hub (or hubs).…”
Section: Cftr Protein Structure Remains To Be Fully Elucidatedmentioning
confidence: 99%